2017
DOI: 10.1016/j.bbrc.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Purification of functional reprogramming factors in mammalian cell using FLAG -Tag

Abstract: Induced pluripotent stem cells (iPSCs) technology is a method for generating pluripotent stem cells in vitro from fully differentiated cells such as fibroblast cells. The potential applications of iPSC technology in cell therapy and disease modeling could influence current medical practices. Despite current advances in iPSC technology, many patient-derived reprogrammed cells are not suitable for clinical trial because most protocols rely on virus-based techniques, which pose the risk of integration of the vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The KEX2syn gene was modified by adding the FLAG-tag, serine, alanine 6 His-tag and a stop codon at the 3'-terminal of the KEX2 gene. The FLAG-tag and the 6 His-tag in the construct play a role in detecting and purifying (Zhao et al 2013;Han et al 2017). Serine and alanine acts as linkers that encode a unique restriction site for fusion with the KEX2syn gene.…”
Section: Discussionmentioning
confidence: 99%
“…The KEX2syn gene was modified by adding the FLAG-tag, serine, alanine 6 His-tag and a stop codon at the 3'-terminal of the KEX2 gene. The FLAG-tag and the 6 His-tag in the construct play a role in detecting and purifying (Zhao et al 2013;Han et al 2017). Serine and alanine acts as linkers that encode a unique restriction site for fusion with the KEX2syn gene.…”
Section: Discussionmentioning
confidence: 99%
“…To generate iPSCs that are free from viral contamination, and also non-integrative systems, considerable progress has been made by transfecting DNA into cells using liposomes or electroporation, such as plasmids, episomal plasmids [ 57 , 58 , 59 , 60 , 61 , 62 ], minicircle DNA [ 63 , 64 ], removable piggyBac transposon followed by Cre transfection [ 65 ] and non-DNA based methods such as synthetic mRNAs [ 66 , 67 ], miRNAs (miR302/367 cluster) [ 68 , 69 ] and recombinant proteins [ 49 , 70 ]. Although proteins or mRNAs can generate iPSC, the protocols are costly and technically challenging.…”
Section: Delivery or Induction Methods Of Oskm Factorsmentioning
confidence: 99%
“…It has low immunogenicity so that purified proteins were directly immunized to animals and antibodies were prepared (Freitas et al, 2022) Bromberg et al (2022) found that His tag can be used as a decoy modulating preferred orientation in cryo-EM, providing a new scheme for improving cryo-EM sample processing Williams et al (2021) used the optimized His tag the integrate with recombinant proteins, which is not only convenient for affinity chromatography, but also provides an effective binding site for the radiolabeling of the recombinant protein. Therefore, the optimized His tag are used in the process of cancer molecular imaging and radionuclide therapy with more economic advantages FLAG DYKDDDDK/1.01 kDa (Mishra, 2020) It has a small molecular weight, high hydrophilicity (Schmidt et al, 2012), The tag has high sensitivity and are easy to remove after use Han et al (2017) purified functional reprogramming factors from HEK293 cells using FLAG tag. Imagawa et al (2021) purified virus-like particles with FLAGtagged envelope protein through one-step affinity purification with FLAG tag, which could be used as a tetravalent dengue vaccine candidate HA YPYDVPDYA/1.1 kDa The tag is derived from the influenza virus hemagglutinin (Zhou et al, 2012).…”
Section: Tags Sequence/size Features Applicationmentioning
confidence: 99%